Do stigma and its psychosocial impact differ between Asian-born Chinese immigrants and Western-born Caucasians with head and neck cancer?. Issue 5 (3rd July 2016) - Lebel, Sophie; Payne, Ada Y. M.; Mah, Kenneth; Irish, Jonathan; Rodin, Gary; Devins, Gerald M.
Abstract: Stigma appears to influence emotional distress and well-being in cancer survivors, but cross-cultural differences have been ignored. Previous studies suggest that stigma may be especially relevant for survivors of Asian origin. However, their study designs (e.g. focused on female cancers, qualitative designs, and an absence of comparison groups) limit the strength of this conclusion. We hypothesized that (1) Asian-born Chinese immigrants (AI) would report more perceived cancer-related stigma than Western-born Caucasians (WBC); and (2) the impact of stigma on emotional distress and well-being would be greater in AI as compared to WBC. Head and neck cancer survivors ( n = 118 AI and n = 404 WBC) completed measures of well-being, emotional distress, and a three-item indicator of stigma in structured interviews. The majority of respondents (59%) reported one or more indicators of stigma. Stigma correlated significantly with emotional distress ( r = .13, p = .004) and well-being ( r = −.09, p = .032). Contrary to our hypotheses, WBCs and AIs did not differ in reported stigma nor did we detect differences in its psychosocial impact. Stigma exerts a deleterious psychosocial impact on head and neck cancer survivors. It did not differ significantly between AI and WBC survivors.